Copper strip for copper-aluminum compounding and short-process processing method thereof

By using aluminum elements uniform doping, horizontal continuous casting, heat treatment, cold rolling, annealing and high surface treatment technologies in the preparation process of copper-aluminum composite copper strips, the process flow is simplified and production efficiency is improved, and the problems of complex processes, time-consuming and poor binding force in the existing technology are solved, thereby achieving high efficiency, low-cost production and excellent mechanical properties of the materials.

CN119635200AActive Publication Date: 2025-03-18ZHONGSE ZHENGRUI (SHANDONG) COPPER CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411885543.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing copper tape preparation process for copper-aluminum composite is complex and time-consuming, and the copper-aluminum composite bonding force is poor, which affects the mechanical properties and application effect of the material.

Method used

The aluminum element homogenized doping, horizontal continuous casting, heat treatment, cold rolling, annealing and high surface treatment technology are used to simplify processing steps, improve production efficiency, and accurately control the grain size through the annealing process to enhance material performance.

Benefits of technology

It realizes efficient and low-cost production of copper tape for copper-aluminum composite, ensuring high surface cleanliness, strong copper-aluminum composite bonding force, and uniform and stable mechanical properties. It is suitable for the field of copper-aluminum composite materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a copper strip for copper-aluminum compounding and a short-process processing method thereof, and belongs to the technical field of copper alloy strip preparation. The copper strip for copper-aluminum compounding is prepared through the procedures of horizontal continuous casting, surface milling, heat treatment, cold rolling, primary cleaning, finished product annealing and finished product cleaning. Horizontal continuous casting and heat treatment processes are adopted for preparation, the red copper casting blank with refined grains is obtained, the hot rolling procedure is omitted, the machining process is simplified, the machining time is shortened, and the production efficiency is improved; an annealing-cleaning synergistic high surface treatment technology is adopted, so that the surface treatment quality and efficiency are improved, and outstanding advantages are shown in the aspect of enhancing the surface smoothness of the material; a trace amount of aluminum is added into the copper strip for copper-aluminum compounding for doping, so that the compounding binding force of the copper strip and the aluminum strip can be improved; and unprecedented high-precision control over the grain size is achieved through the annealing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloy strip preparation, and in particular relates to a copper strip for copper-aluminum composite and a short-process processing method thereof. Background Art

[0002] Copper / aluminum bimetallic composite strip is a composite material made of copper and aluminum through rolling, compounding, heat treatment and other processes. Compared with copper strip, copper-aluminum composite strip not only maintains the good electrical and thermal conductivity of copper strip, but also takes advantage of the light weight, easy processing and corrosion resistance of aluminum strip. It is cost-effective and low cost, and is widely used in the fields of electricity, new energy vehicles, construction, etc. Among various copper-aluminum composite methods, rolling composite method has become one of the current mainstream production methods due to its low cost, high processing efficiency and simple operation.

[0003] The rolling composite method is a commonly used process for copper-aluminum composite strips. The main problems in its production are as follows: First, it is necessary to ensure that the copper-aluminum composite has sufficient bonding strength; second, the uneven plastic deformation of the copper strip and the aluminum strip during the copper-aluminum composite rolling process causes the uneven copper-aluminum thickness ratio. There are also studies on copper-aluminum composite red copper strips in the prior art. For example, China CN117259463 A discloses a copper-aluminum composite red copper strip and its preparation method and application. The copper-aluminum composite red copper strip is prepared with copper alloy raw materials, smelting, semi-continuous casting, hot rolling, milling, rough rolling, primary cleaning, fine rolling, secondary cleaning, finished product annealing, finished product cleaning, and the glossiness and crystal form of the strip surface are regulated to eliminate the stress in the strip processing project. The copper strip can be well composited with aluminum metal. The method for preparing copper-aluminum composite red copper strips in this patent has many processes, complex procedures, and is time-consuming. Summary of the invention

[0004] In view of the problems of the prior art that the preparation process of copper strip for copper-aluminum composite is complicated, time-consuming and the copper-aluminum composite bonding strength is poor, the present invention provides a copper strip for copper-aluminum composite and a short-process processing method thereof, which simplifies the processing steps through aluminum element uniform doping, horizontal continuous casting, heat treatment, cold rolling, annealing and high surface treatment technology, and ensures that the surface of the copper strip for copper-aluminum composite is clean, the copper-aluminum composite bonding strength is strong, and the mechanical properties are uniform and stable while achieving efficient and low-cost production of the copper strip for copper-aluminum composite.

[0005] The present invention is achieved through the following technical solutions: A short-process processing method for a copper strip for copper-aluminum composite includes the following steps: (1) Horizontal continuous casting: The raw materials are added into a horizontal continuous casting melting furnace for melting, the melting temperature is controlled at 1100-1160°C, the molten copper is transferred from a converter to a holding furnace, the temperature of the holding furnace is controlled at 1160-1200°C; the copper ingot is obtained through a graphite crystallizer; (2) Milling: Step (2) milling the ingot after heat treatment to remove the oxide scale on the surface; (3) Heat treatment: The ingot in step (1) is heat treated at 550-680°C; (4) Cold rolling: The milled ingot is cold rolled, with a cold rolling processing rate of 70-90% and a roller roughness of Ra 0.2-0.4 μm; (5) Primary cleaning: After step (4), the cold-rolled strip is cleaned once to remove the residual emulsion on the surface. (6) Finished product annealing: the strip cleaned in step (5) is annealed at a temperature of 380 to 500°C for a time of 3 to 8 hours; (7) Cleaning of finished products.

[0006] Furthermore, the raw materials in step (1) are electrolytic copper and electrolytic aluminum; the mass percentage composition of the components in the ingot is: P: 0.001-0.005wt%, Fe: 0.001-0.005wt%, Al: 0.001-0.01wt%, impurities are less than 0.01%, and the balance is Cu.

[0007] Furthermore, the heat treatment time in step (3) is 2-3 hours, and the heating rate is 80-100°C / h.

[0008] Furthermore, in step (2), the milling thickness of the upper and lower surfaces is 0.6-1.0 mm, and the single-sided milling thickness of the side is 0.8-1.5 mm.

[0009] Furthermore, the first cleaning in step (5) and the finished product cleaning in step (7) are performed with nylon yarn of 600-1000 mesh, the cleaning speed is 20-40 m / min, and the pressure reduction is 18-30A.

[0010] Furthermore, the curling tension in step (5) the primary cleaning and step (7) the finished product cleaning is 8000-12000 KN, and the smaller winding tension ensures that the strip does not stick after annealing in the bell furnace.

[0011] Furthermore, in step (6), the finished product annealing atmosphere is a nitrogen-hydrogen mixed gas containing 60-90% hydrogen. The high hydrogen content atmosphere is used to ensure that hydrogen reduces the oxide film on the surface of the strip, and to control the glossiness of the strip surface for subsequent finished product cleaning.

[0012] Furthermore, the heating rate of the finished product annealing in step (6) is 50-100°C / h.

[0013] In the present invention, the copper strip for copper-aluminum composite is obtained by processing using the processing method.

[0014] Furthermore, the copper strip for copper-aluminum composite has a grain size of 10-18 μm, a Vickers hardness of 65-75, a surface glossiness parallel to the rolling direction lower than 350 GU, and a surface glossiness perpendicular to the rolling direction lower than 180 GU.

[0015] Beneficial Effects (1) Compared with the prior art, the present invention adopts horizontal continuous casting and heat treatment (heat treatment after milling) process to obtain a copper ingot with refined grains. Compared with the semi-continuous casting process, the hot rolling process is omitted, the processing steps are simplified, the hot rolling passes and cleaning are reduced, the processing time is effectively reduced, and the production efficiency is improved; (2) The present invention adopts the high surface treatment technology of annealing-cleaning synergy, which significantly improves the quality and efficiency of surface treatment. Moreover, with its unique synergistic mechanism, it shows extraordinary advantages in enhancing the surface finish of materials. The copper strip prepared by it can be better applied in the field of copper-aluminum composite; (3) The present invention can improve the bonding strength of the copper strip and the aluminum strip by adding a trace amount of aluminum to the copper strip for copper-aluminum composite. (4) The annealing process of the present invention, such as heating temperature, holding time and heating rate, achieves unprecedented high-precision control of grain size. DETAILED DESCRIPTION

[0016] The present invention is described in detail below through implementation cases, but it should be noted that these implementation cases are not limitations of the present invention, and any equivalent transformations or substitutions in functions, methods, or structures made by ordinary technicians in the field according to these implementation methods are all within the protection scope of the present invention.

[0017] Example 1 (1) Horizontal continuous casting: a certain proportion of electrolytic copper and electrolytic aluminum are added to a horizontal continuous casting smelting furnace for melting, the smelting temperature is controlled at 1140°C, the copper liquid is transferred from the furnace to a holding furnace, and the temperature of the holding furnace is controlled at 1180°C; a copper ingot is obtained through a graphite crystallizer; the mass percentage composition of the ingot is: Fe: 0.002%, P: 0.0013, Al: 0.0025wt%, the total impurities are less than 0.1%, the balance is copper, and the thickness of the ingot is 16.8mm; (2) Milling: The ingot in step (1) is milled, with a milling amount of 0.6 mm per side and a side milling thickness of 1.2 mm per side, to remove the surface oxide scale; (3) Heat treatment: The milled ingot is heat treated at 600°C, with a heating rate of 100°C / h and a heat treatment time of 2.5h; (4) Cold rolling: The ingot after heat treatment is cold rolled, the cold rolling processing rate is 82%, the roll roughness Ra is 0.26 μm, and the copper strip with a thickness of 2.8 mm is obtained; (5) Primary cleaning: The cold-rolled strip of step (4) is cleaned once, using a nylon wire brush with a mesh size of 800, a cleaning speed of 24 m / min, a brush pressing current of 16 A, and a curling tension of 10000 KN to wash away residual emulsion on the surface; (6) Finished product annealing: annealing the strip cleaned in step (5) in a bell-type furnace at a heating rate of 80°C / h, an annealing temperature of 470°C, an annealing time of 5h, and an annealing atmosphere of a nitrogen-hydrogen mixed gas containing 80% hydrogen; (7) Finished product cleaning: A nylon wire brush with a mesh size of 800 is used for cleaning. The cleaning speed is 24 m / min, the brush pressing current is 16 A, and the curling tension is 10000 KN to obtain a copper strip for copper-aluminum composite.

[0018] Example 2 (1) Horizontal continuous casting: a certain proportion of electrolytic copper and electrolytic aluminum are added to a horizontal continuous casting smelting furnace for melting, the smelting temperature is controlled at 1140°C, the copper liquid is transferred from the furnace to a holding furnace, and the temperature of the holding furnace is controlled at 1180°C; a copper ingot is obtained through a graphite crystallizer; the mass percentage composition of the ingot is: Fe: 0.002%, P: 0.0013, Al: 0.0025wt%, the total impurities are less than 0.1%, the balance is copper, and the thickness of the ingot is 16.8mm; (2) Milling: The ingot in step (1) is milled, with a milling amount of 0.6 mm per side and a side milling thickness of 1.2 mm per side, to remove the surface oxide scale; (3) Heat treatment: The milled ingot is heat treated at 650°C, with a heating rate of 80°C / h and a heat treatment time of 3h; (4) Cold rolling: The ingot after heat treatment is cold rolled, the cold rolling processing rate is 82%, the roll roughness Ra is 0.26 μm, and the copper strip with a thickness of 2.8 mm is obtained; (5) Primary cleaning: The cold-rolled strip of step (4) is cleaned once, using a nylon wire brush with a mesh size of 800, a cleaning speed of 24 m / min, a brush pressing current of 16 A, and a curling tension of 10000 KN to wash away residual emulsion on the surface; (6) Finished product annealing: the strip cleaned in step (5) is annealed in a bell-type furnace at a heating rate of 100°C / h, an annealing temperature of 450°C, an annealing time of 4h, and an annealing atmosphere of a nitrogen-hydrogen mixed gas containing 80% hydrogen; (7) Finished product cleaning: A nylon wire brush with a mesh size of 800 is used for cleaning. The cleaning speed is 24 m / min, the brush pressing current is 16 A, and the curling tension is 10000 KN to obtain a copper strip for copper-aluminum composite.

[0019] Example 3 (1) Horizontal continuous casting: a certain proportion of electrolytic copper and electrolytic aluminum are added to a horizontal continuous casting smelting furnace for melting, the smelting temperature is controlled at 1140°C, the copper liquid is transferred from the furnace to a holding furnace, and the temperature of the holding furnace is controlled at 1180°C; a copper ingot is obtained through a graphite crystallizer; the mass percentage composition of the ingot is: Fe: 0.002%, P: 0.0013, Al: 0.0025wt%, the total impurities are less than 0.1%, the balance is copper, and the thickness of the ingot is 16.8mm; (2) Milling: The ingot in step (1) is milled, with a milling amount of 0.6 mm per side and a side milling thickness of 1.2 mm per side, to remove the surface oxide scale; (3) Heat treatment: The milled ingot is heat treated at 580°C, with a heating rate of 100°C / h and a heat treatment time of 2.5h. (4) Cold rolling: The ingot after heat treatment is cold rolled, the cold rolling processing rate is 82%, the roll roughness Ra is 0.26 μm, and the copper strip with a thickness of 2.8 mm is obtained; (5) Primary cleaning: The cold-rolled strip of step (4) is cleaned once, using a nylon wire brush with a mesh size of 800, a cleaning speed of 24 m / min, a brush pressing current of 16 A, and a curling tension of 10000 KN to wash away residual emulsion on the surface; (6) Finished product annealing: the strip cleaned in step (5) is annealed in a bell-type furnace at a heating rate of 60°C / h, an annealing temperature of 400°C, an annealing time of 6h, and an annealing atmosphere of a nitrogen-hydrogen mixed gas containing 80% hydrogen; (7) Finished product cleaning: A nylon wire brush with a mesh size of 800 is used for cleaning. The cleaning speed is 24 m / min, the brush pressing current is 16 A, and the curling tension is 10000 KN to obtain a copper strip for copper-aluminum composite.

[0020] Comparative Example 1 (1) Semi-continuous casting: a certain proportion of electrolytic copper and electrolytic aluminum are added into a horizontal continuous casting furnace for melting, and processed into ingots by semi-continuous casting; the mass percentage composition of the ingot components is: Fe: 0.002%, P: 0.0013, Al: 0.0025wt%, the total impurities are less than 0.1%, and the balance is copper; (2) Hot rolling: The ingot in step (1) is heated in a walking beam furnace for 4.5 h and then taken out of the furnace. The ingot at 760° C. is hot rolled to obtain a hot-rolled billet with a thickness of 16.8 mm after 8 hot rolling passes. (3) Milling: The ingot after heat treatment in step (2) is milled, with a milling amount of 0.6 mm per side and a side milling thickness of 1.2 mm per side, to remove the surface oxide scale; (4) Cold rolling: The milled ingot is cold rolled with a cold rolling rate of 82% and a roller roughness of Ra 0.26 μm to obtain a copper strip with a thickness of 2.8 mm. (5) Primary cleaning: The cold-rolled strip of step (4) is cleaned once, using a nylon wire brush with a mesh size of 800, a cleaning speed of 24 m / min, a brush pressing current of 16 A, and a curling tension of 10000 KN to wash away residual emulsion on the surface; (6) Finished product annealing: the strip cleaned in step (5) is annealed in a bell-type furnace at a heating rate of 80°C / h, an annealing temperature of 400°C, an annealing time of 5h, and an annealing atmosphere of a nitrogen-hydrogen mixed gas containing 80% hydrogen; (7) Finished product cleaning: A nylon wire brush with a mesh size of 800 is used for cleaning. The cleaning speed is 24 m / min, the brush pressing current is 16 A, and the curling tension is 10000 KN to obtain a copper strip for copper-aluminum composite.

[0021] Comparative Example 2 Compared with Example 1, the finished product annealing temperature in step (6) of Comparative Example 2 was set to 570° C., the annealing time was 5 h, and the remaining operations were the same as in Example 1, to obtain a 2.8 mm copper-aluminum composite copper strip.

[0022] Comparative Example 3 Compared with Example 1, in Example 3, step (3) is not performed, and the horizontal continuous casting ingot is directly cold rolled after surface milling. The remaining operations are the same as those in Example 1, and a 2.8 mm copper-aluminum composite copper strip is obtained.

[0023] Comparative Example 4 Compared with Example 1, in step (1) of Comparative Example 4, no trace aluminum element is doped (i.e., no electrolytic aluminum is added), and the composition by weight percentage of the ingot composition is: Fe: 0.002%, P: 0.0013, Al: 0.0025wt%, the total impurities are less than 0.1%, and the remainder is copper; the remaining operations are the same as in Example 1, and a 2.8 mm copper-aluminum composite copper strip is obtained.

[0024] Performance Test: The grain size, hardness and surface glossiness of the 2.8 mm copper strips for copper-aluminum composites prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested, and the results are shown in Table 1 below. As can be seen from Table 1, the cleanliness and mechanical properties of the copper strips for copper-aluminum composites prepared by the present invention are controllable, the grains are refined, and the trace uniform doping of aluminum can be better applied to the field of copper-aluminum composite materials.

[0025] Table 1 Performance test table of copper strip for copper-aluminum composite .

Claims

1. A short-process processing method for copper strip for copper-aluminum composite, characterized in that: The following steps are involved: (1) Horizontal continuous casting: The raw materials are added into a horizontal continuous casting melting furnace for melting, the melting temperature is controlled at 1100-1160°C, the molten copper is transferred from a converter to a holding furnace, the temperature of the holding furnace is controlled at 1160-1200°C; the copper ingot is obtained through a graphite crystallizer; (2) Milling: Step (2) milling the ingot after heat treatment to remove the oxide scale on the surface; (3) Heat treatment: The ingot in step (1) is heat treated at 550-680°C; (4) Cold rolling: The milled ingot is cold rolled, with a cold rolling processing rate of 70-90% and a roller roughness of Ra 0.2-0.4 μm; (5) Primary cleaning: After step (4), the cold-rolled strip is cleaned once to remove the residual emulsion on the surface. (6) Finished product annealing: the strip cleaned in step (5) is annealed at a temperature of 380 to 500°C for a time of 3 to 8 hours; (7) Cleaning of finished products.

2. The short-process processing method of the copper strip for copper-aluminum composite according to claim 1 is characterized in that: The raw materials in step (1) are electrolytic copper and electrolytic aluminum; the mass percentage of each component in the ingot is: P: 0.001-0.005wt%, Fe: 0.001-0.005wt%, Al: 0.001-0.01wt%, impurities are less than 0.01%, and the balance is Cu.

3. The short-process processing method of the copper strip for copper-aluminum composite according to claim 1 is characterized in that: The heat treatment time of step (3) is 2-3 hours, and the heating rate is 80-100°C / h.

4. The short-process processing method of the copper strip for copper-aluminum composite according to claim 1 is characterized in that: In step (2), the milling thickness of the upper and lower surfaces is 0.6-1.0 mm, and the single-sided milling thickness of the side is 0.8-1.5 mm.

5. The short-process processing method of the copper strip for copper-aluminum composite according to claim 1, characterized in that: The first cleaning of step (5) and the finished product cleaning of step (7) are performed with nylon wire of 600-1000 mesh, the cleaning speed is 20-40 m / min, and the pressure reduction is 18-30A.

6. The short-process processing method of the copper strip for copper-aluminum composite according to claim 1, characterized in that: The curling tension of step (5) one-time cleaning and step (7) finished product cleaning is 8000~12000KN. The smaller winding tension ensures that the strip does not stick after annealing in the bell furnace.

7. The short-process processing method of the copper strip for copper-aluminum composite according to claim 1 is characterized in that: The atmosphere for annealing the finished product in step (6) is a nitrogen-hydrogen mixed gas containing 60-90% hydrogen. The high hydrogen content atmosphere is used to ensure that hydrogen reduces the oxide film on the surface of the strip. This is to control the glossiness of the strip surface for subsequent finished product cleaning.

8. The short-process processing method of the copper strip for copper-aluminum composite according to claim 1, characterized in that: The heating rate of the finished product annealing in step (6) is 50-100°C / h.

9. A copper strip for copper-aluminum composite obtained by the processing method according to any one of claims 1 to 8.

10. The copper strip for copper-aluminum composite according to claim 9, characterized in that: The copper strip for copper-aluminum composite has a grain size of 10-18 μm, a Vickers hardness of 65-75, a surface glossiness parallel to the rolling direction lower than 350 GU, and a surface glossiness perpendicular to the rolling direction lower than 180 GU.

Citation Information

Patent Citations

  • Short-flow efficient production method of pure copper tube

    CN102304686A

  • Copper alloy antibacterial material and processing technique thereof

    CN102816947A

  • Copper-clad aluminum-red copper belt production technology

    CN104630789A

  • Short-process high-performance oxygen-free copper strip production method

    CN105729064A

  • Preparation method for abrasion-resistant brass alloy copper belt

    CN106048482A